2010
DOI: 10.1097/opx.0b013e3181fef3a9
|View full text |Cite
|
Sign up to set email alerts
|

Reported Wearing Compliance of Ready-Made Spectacles at 6 and 12 Months

Abstract: Our findings suggest that spectacle wearing compliance studies will not be comparable unless a standard time frame is used to assess compliance. We found assessing self-reported compliance to be a useful tool in guiding our program. Understanding the reasons for non-compliance will help guide corrective action and planning of interventions designed to increase wearing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Other studies in which spectacles were provided free of charge have also found loss, breakage, or scratched lenses to be one of the main reasons given for not wearing their spectacles. 4, 6, 9, 21 Fear that glasses will make their vision worse 11-13 , parental disapproval 10, 13 , concern over appearance or being teased 4, 10, 11 , and leaving glasses at home or only wearing glasses part-time 6, 8 have also been found to be major reasons for non-compliance with spectacle wear. Unfortunately, we did not collect data on how many students actually received their replacement spectacles, nor did we specifically ask the students if they had broken or lost both pairs of spectacles.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in which spectacles were provided free of charge have also found loss, breakage, or scratched lenses to be one of the main reasons given for not wearing their spectacles. 4, 6, 9, 21 Fear that glasses will make their vision worse 11-13 , parental disapproval 10, 13 , concern over appearance or being teased 4, 10, 11 , and leaving glasses at home or only wearing glasses part-time 6, 8 have also been found to be major reasons for non-compliance with spectacle wear. Unfortunately, we did not collect data on how many students actually received their replacement spectacles, nor did we specifically ask the students if they had broken or lost both pairs of spectacles.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on this subject have assessed spectacle use over periods of a month to a year, and relied on a variety of outcomes, including self-reported use; [20][21][22] estimates by parents, teachers, or health professionals; 18 and directly observed wear. 3,6,7,[23][24][25] Observed rates of wear were low, ranging from 13% to 41%.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 99%
“…3,6,7,[23][24][25] Observed rates of wear were low, ranging from 13% to 41%. 3,6,7,21,23,24 All of the few studies reporting higher rates (46% by Keay and associates in China, 25 56% by Vincent and associates in Thai refugee camps, 22 and 58% by von-Bischhoffshaussen and associates in Chile 20 ) relied on self-report and/or estimates of teachers or parents, 20,22 and had low (58%-76%) rates of follow-up 20,22 or assessment times as short as 1 month after spectacle distribution. 25 It would appear that longer-term (over the course of a school year) compliance with free spectacles, as measured by objective indicators such as observed wear at unannounced examinations, is low among children without additional interventions.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 99%
“…Future research should seek to attain longer follow-up as long-term spectacle acceptance may not mirror our 1 month results. 34 Important strengths of the study include randomized design, large sample size, low loss to follow-up, and use of validated visual function instrument.…”
Section: Discussionmentioning
confidence: 99%